Pengaruh Pupuk Hayati Endofitik Dengan Azolla Pinnata Terhadap Serapan N , N-Total Tanah, Dan Bobot Kering Tanaman Padi (Oryza Sativa L.) Pada Tanah Salin - Alin Kusumah Dewi; Mieke Rochimi Setiawati (Faculty of Agriculture, Pattimura University, 2017)
Saline soil contain excessive NaCl content which inhibit plant growth and lead to nitrogen deficiency. Endophytic bacteria live inside the plant tissue and has the ability to fix nitrogen directly from the atmosphere, meanwhile Azolla pinnata can be used as organic ameliorant that able to increase the number of availability nitrogen for plant in soil, and improve the physical, chemical, and biological properties of soil. The aims of this experiment were to find out the treatment that cause highest nitrogen uptake by plant, total-N of soil, and dry weight of rice in saline soil. The experimental design was randomized block design with eight treatments and four repetitions. The results showed that the application of biofertilizer and ameliorant increased nitrogen uptake by plant and dry weight of rice in saline soil, but there was no significant effect on total-N of soil. This experiment suggested that endophytic bacteria biofertilizer and Azolla pinnata were effective to increase dry weight and nitrogen uptake of rice grown in soil with EC between 2 dS m-1 - 4 dS m-1.